Long‐term trajectory of acquired demyelinating syndrome and multiple sclerosis in children. (3rd May 2021) - Eusebi, Anna; Zara, Pietro; Zarbo, Ignazio Roberto; Festa, Silvia; Dessì, Veronica; Pes, Valentina; Salis, Francesca; Sotgiu, Giovanni; Carta, Alessandra; Sotgiu, Stefano
Abstract : Aim: We assessed the frequency, characteristics, and future trajectory of monophasic acquired demyelinating syndromes (ADS) associated with conversion to paediatric multiple sclerosis. Method: This was a retrospective observational study of Sardinian children (<18y of age) with onset of ADS between 2001 and 2018. Results: We identified 44 children with ADS (21 males, 23 females; median age at onset 16y, range 4mo–18y), 21 of whom were already presenting with criteria for paediatric multiple sclerosis. The mean crude prevalence of ADS in Sardinian children was 59.2 per 100 000, while incidence was 3.1 per 100 000 per year (1.3 in children aged ≤10y and 11.9 in those aged 10–17y). After a mean (SD) follow‐up of 8 years 5 months (5y 4mo), the most common ( n =32) trajectory was conversion to paediatric multiple sclerosis. At onset, the total prevalence and mean annual incidence of paediatric multiple sclerosis were 35.6 per 100 000 and 2.3 per 100 000 respectively (0.5 in individuals aged ≤10y, 10.0 in the older group). Interpretation: Sardinia is a very high risk area for ADS in children. Nearly half of this population can already be diagnosed with paediatric multiple sclerosis at onset. Overall, 72% of those with ADS will have paediatric multiple sclerosis after a mean of 8 years. What this paper adds Sardinia is a very high risk area for paediatric acquired demyelinating syndromes (ADS). A high proportion of those with paediatric multiple sclerosis are diagnosed at onset of ADS. After an average 8 years from onset of paediatric ADS, three‐quarters of patients are diagnosed with paediatric multiple sclerosis. What this paper adds: Sardinia is a very high risk area for paediatric acquired demyelinating syndromes (ADS). A high proportion of those with paediatric multiple sclerosis are diagnosed at onset of ADS. After an average 8 years from onset of paediatric ADS, three‐quarters of patients are diagnosed with paediatric multiple sclerosis.